Patient views on the implementation of artificial intelligence in radiotherapy. (May 2023) - Temple, S.; Rowbottom, C.; Simpson, J.
Abstract: Purpose/objective: To date there has been limited research looking at patient views on the implementation of artificial intelligence (AI) in radiotherapy. The aim of this study is to adapt and utilise a validated patient questionnaire to develop an understanding of current patient views on the use of AI in radiotherapy. Materials/methods: An existing questionnaire, developed to assess understanding of patients' views on the implementation of AI in radiology, was adapted to the field of radiotherapy. The questionnaire was distributed to cancer patients receiving radiotherapy treatment between November 2021 and March 2022. Completed questionnaires were analysed to assess patient levels of positivity or negativity towards AI. Results were grouped into five factors, representing underlying patient perspectives, and correlation of factors with demographic variables was assessed. Results: In total, 95 patients participated. Overall, there was a moderately negative patient view towards the use of AI in radiotherapy. Certain factors drew a more negative response than others, for example patients desire significant personal interaction with healthcare professionals during the course of their treatment. No significant correlation was found between the demographics of age and gender and the strength of views towards the use of AI in radiotherapy. Conclusion: This study has found that there are clear patient concerns around the use of AI in radiotherapy. As the use of AI in this field increases in future years, it will therefore be extremely important to educate and involve patients in the future direction of this technology.